(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper aims at the prospect of developing a fully automated parking system for two wheelers and cars. This proposed system improvises upon the existing parking system by enhancing its security features and automating the parking process thus eliminating the need for manual intervention. For authentication and owner identification the parking system has an inbuilt Bluetooth reader. The user has to start his/her mobile’s Bluetooth for identification and registration. The Bluetooth reader fetches the user’s Bluetooth number and transfers it to database. The user has to re-start his/her Bluetooth at the time of exit. This eliminates the use of tokens or paper bills. The space management and automation is performed with the help of an ARM microcontroller which controls the mechanical motors to park the vehicle at an appropriate parking location [5].